The sorcerer of the north - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2009)
A fantasy tale in which several years pass, and Will, now a committed Ranger, learns of the illness of Lord Syron and travels with his friend Alyss to see who is still loyal to the lord or who is planning to destroy him. Suddenly Alyss is kidnapped and now Will must make a choice between being loyal to his mission or being supportive of his friend.